Using Green Roof Concept As A Passive Design Technology To Minimise The Impact Of Global Warming - Ismail, Asmat; Samad, Muna Hanim; Rahman, Abdul Malek Abdul (2008)

(untitled)
Global warming phenomenon or climate change has grabbed people attention worldwide. This phenomenon leads to many environmental issues including, higher atmospheric temperatures, intensive precipitation and increase greenhouse gaseous emission. Sea level rising, melting of ice sheets, drought, hurricane are also the effect of global warming.